What Contributes to an Attractive Local Political Office? Evidence from Municipal Council Elections in Switzerland - Tobias Schib; Alois Stutzer (Institute of Labor Economics (IZA), 2024)
Small-scale federal democracies depend on the active participation of individuals in local political office. Both anecdotal evidence and empirical studies across Western democracies indicate a growing difficulty in recent decades to recruit candidates for municipal offices. This study examines the impact of monetary compensation and workload on the supply of candidates for municipal councils, drawing on the economic theory of political selection. Using data from municipal elections in over 500 municipalities across three Swiss cantons since the 1970s, we apply two-way fixed effects models to analyze the relationship between compensation, workload, and candidate supply. Our findings show that higher salaries do not lead to more competitive local elections or longer terms in office. However, reducing the workload associated with municipal mandates appears to be a more effective strategy for increasing candidate supply, particularly in recruiting women.
Keywords: D72; J45; 330; political selection; candidate pool; compensation for public office; local council; workload